Cellulose nanocrystal reinforced thermoplastic polyurethane nanocomposites - Amin, Khairatun Najwa Mohd; Beg, M. D.H.; Yusoh, K.; Sulaiman, Nurul Sa Aadah; Nafsun, Aainaa Izyan (2019)
Thermoplastic polyurethane (TPU) is one of the most widely used thermoplastic elastomers (TPE) due to its high strength and tear resistance, good elasticity, flexibility and damping properties. Enhancement of TPU properties can be achieved by either varying the hard-soft segment composition ratio or by the reinforcement with micro or nanoscale fillers. In the last decade, cellulose nanocrystals (CNC) have gained an increasing degree of interest from both academics and industries as ‘sustainable nanomaterials’, as they have high-axial mechanical properties and reinforcing capability, abundance, low density, renewability and biodegradability. Contemporary research activities centred on the reinforcement of TPU with CNC have typically employed solvent-based fabrication methods (solution/wet casting). For the successful translation of this new class of nanocomposite materials from laboratory research to widespread applications, processing via scalable approaches has to be demonstrated. The utility of CNC as TPU reinforcers has also been limited by the poor thermal stability of CNC, which are typically isolated via acid hydrolysis, as well as the poor quality of dispersion achieved when more scalable methodologies are used (eg. melt compounding). Thus, this study firstly aims to explore, optimise and develop CNC with enhanced thermal stability, and secondly, to incorporate these more thermostable CNC into high performance TPU nanocomposites via scalable melt-compounding method. The report is presented in two main parts. The first part is focused on the production/isolation of CNC with enhanced thermal stability. CNC has been isolated via two methods, acid hydrolysis using mild acid and a scalable high energy bead milling process. Both processes have been optimised to isolate CNC with requisite thermal stability and dispersibility for TPU host polymers. The second part is focused on the processability of CNC into the TPU matrix via an intermediate-scale traditional twin screw extrusion melt compounding method as well as masterbatch process to improve the dispersibility of CNC in TPU. The main outcomes or observations from this study are:are:  Isolation of CNC with enhanced thermal stability and dispersibility via mild, mixed acid hydrolysis and mechanical method.  Improved dispersibility using masterbatch process in incorporating CNC and TPU which is suitable to be implied for industrial scale.  The performance of the host TPU matrix, a “workhorse” aromatic polyether grade, is remarkably enhanced by the incorporation strategies reported, without negatively affecting the important elastic properties and compliance of the TPU.